2012
DOI: 10.1074/jbc.m111.310581
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-induced Interleukin-6 Gene Transcription in Skeletal Muscle Is Regulated by c-Jun Terminal Kinase/Activator Protein-1

Abstract: Background: IL-6 is up-regulated by contraction in skeletal muscle. Results: Contraction-induced IL-6 expression is blunted by JNK inhibition. Conclusion:The JNK/AP-1 pathway regulates IL-6 expression in contracting muscle. Significance: This highlights a novel contraction-mediated transcriptional pathway for IL-6 in skeletal muscle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 32 publications
2
77
0
2
Order By: Relevance
“…Evidence for this has been provided by a study showing that the NFκB signalling pathway is not activated after exercise and that binding of the p65 subunit of NFκB to the Il-6 promoter decreases with skeletal muscle contraction [14]. Results obtained in C2C12 myotubes and mice suggest that contraction-induced IL-6 expression is mediated by activation of c-Jun N-terminal kinase (JNK) and activator protein 1 (AP1) [14].…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 76%
See 1 more Smart Citation
“…Evidence for this has been provided by a study showing that the NFκB signalling pathway is not activated after exercise and that binding of the p65 subunit of NFκB to the Il-6 promoter decreases with skeletal muscle contraction [14]. Results obtained in C2C12 myotubes and mice suggest that contraction-induced IL-6 expression is mediated by activation of c-Jun N-terminal kinase (JNK) and activator protein 1 (AP1) [14].…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 76%
“…An important source of circulating IL-6 in obesity is the expanding visceral adipose tissue mass. Expression of IL-6 by macrophages within the adipose tissue is dependent on activation of the NFκB signalling pathway, whereas intramuscular IL-6 expression is regulated by different signalling cascades involving Ca 2+ , nuclear factor of activated T cells [83], calcineurin [84], p38 MAPK signalling [85] and JNK/AP1 [14]. These observations led investigators to question the functional role of IL-6 after exercise and in inflammatory conditions (reviewed in detail by Pedersen et al [13]).…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
“…28 We previously reported that myogenesis response to muscle injury was blunted in IL-6 knockout mice, 29 which proved the positive effect of IL-6 on myogenesis. Other groups have also reported that electrical stimulation increases IL-6 in both cultured C2C12 cells 30 and human primary muscle cells. 31,32 In patients with CKD, Caglar et al 33 found that the increase in IL-6 concentration was modest during hemodialysis (14%) but that the levels increased dramatically at the end of the 2-hour posthemodialysis period (68% higher compared with baseline).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we established an advanced in vitro muscle contraction model using cultured myotubes displaying vigorous EPSevoked contractile activity [17,18,21]. This model has increasingly been utilized by other researchers for investigating molecular mechanisms underlying various biological responses induced by actual contractile activity of muscle cells [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%